Avaliação da qualidade protéica de uma dieta estabelecida em Quissamã, Rio de Janeiro, adicionada ou não de multimistura e de pó de folha de mandioca Protein quality evaluation of a diet established in Quissamã, Rio de Janeiro, Brazil, added or not with multi-mixture and powder of cassava leaf - Gilson Teles BOAVENTURA (Revista de Nutrição, 2000)
O trabalho avaliou a qualidade protéica da dieta consumida por crianças desnutridas do município de Quissamã, Rio de Janeiro, e adicionada da multimistura ou do pó de folha de mandioca, utilizando 48 Rattus norvergicus, Wistar, machos, com 24 dias, pesando 58,95 g, recebendo água e ração ad libitum. Na primeira fase, denominada de Desnutrição, os animais foram distribuídos em grupo controle, alimentados com ração à base de caseína, grupo Quissamã alimentados com ração à base da dieta estabelecida em Quissamã, ambos com n=8 animais, e grupo aprotéico com n=32, recebendo uma dieta isenta de proteínas durante 10 dias. Na segunda fase, denominada de Recuperação, com duração de 18 dias, o grupo central e o grupo Quissamã permaneceram recebendo a mesma ração. O grupo aprotéico foi desmembrado em grupo desnutrido controle, alimentado com a mesma ração do grupo central e grupo desnutrido Quissamã, alimentado com a mesma ração do grupo Quissamã e mais dois grupos desnutridos recebendo a ração do grupo desnutrido Quissamã adicionada com o pó de folha de mandioca (grupo desnutrido Quissamã + folha de mandioca) e da multimistura (grupo desnutrido Quissamã + multimistura). Para o grupo controle e o grupo Quissamã foram determinados o Coeficiente de Eficácia Protéica e a Razão Protéica Líquida, nos quais o grupo controle mostrou diferenças significativas em relação ao grupo Quissamã que obteve Razão Protéica Líquida e Coeficiente de Eficácia Protéica relativos de 71,54% e 66,04%, respectivamente. Para os grupos desnutridos foi determinado Coeficiente de Eficácia Proteíca modificado, sendo o grupo desnutrido controle diferente significativamente dos grupo desnutrido Quissamã, grupo desnutrido Quissamã + folha de mandioca e grupo desnutrido Quissamã + multimistura que apresentaram Coeficiente de Eficácia Protéica relativo de 78,10%, 75,72% e 74,67% respectivamente. Conclui-se que a adição da multimistura ou do pó de folha de mandioca não causou impacto sobre a qualidade da dieta estabelecida em Quissamã, não tendo melhorado sua capacidade de recuperar a desnutrição. The following experiment tested the quality of proteins present in the diet of undernourished children in the city of Quissamã, Rio de Janeiro, and then conducted the same tests adding variables: multi-mixture or powder of cassava leaf. The subjects used were 48 Rattus norvergicus, Wistar, males, 24 days old, and weighing 58.95 g. They were fed water and ration ad libitum. In the first phase, called Undernourishment, the animals were divided into three groups: control group, Quissamã group and no proteins group. The control group was fed a ration based on casein and the Quissamã group was fed a ration based on the Quissamã diet. Both of these groups had 8 rats. The no proteins group, with 32 animals, was fed during 10 days a diet with no proteins. In the second phase, called Recovery, which lasted for 18 days, the control group and Quissamã group were fed the same diet. The no proteins group was subdivided into four groups: the undernourished control group, which was fed the same diet as that of the control group; the undernourished Quissamã group, which was fed the same diet as that of the Quissamã group; the undernourished Quissamã group plus powder of cassava leaf; and the undernourished Quissamã group plus multi-mixture. Then, the Protein Efficiency Ratio and the Net Protein Retention were determined for both the control group and the Quissamã group. The results showed significant statiscal differences between these two groups, with the Quissamã Group reaching relative Net Protein Retention and Protein Efficiency Ratio of 71.54% and 66.04 respectively, in relation to the control Group. The Protein Efficiency Ratio Modified was determined for the undernourished groups. The undernourished control group showed significant statiscal differences in relation to the other groups. In this case, the undernourished Quissamã group, the undernourished Quissamã group plus powder of cassava leaf and the undernourished Quissamã group plus multi-mixture reached Relative Protein Efficiency Ratio Modified of 78.10%, 75.72% and 74.67% respectively in relation to the undernourished control group. These tests showed that the presence of the multi-mixture or the powder of cassava leaf in the Quissamã diet had no positive effects in the diet quality since there were no signs of improvement of undernourishment in the animals tested.